1987
DOI: 10.1007/bf01784779
|View full text |Cite
|
Sign up to set email alerts
|

Oesophageal echocardiography

Abstract: The diagnostic value of oesophageal echocardiography is most striking in patients in whom precordial studies are of inadequate quality or fail to establish a definitive diagnosis. Oesophageal studies have excellent image quality, can be completed within 10 minutes without complications and, in most instances, enables the clinical question to be answered. In 50 patients referred for suspected thoracic aorta pathology, oesophageal echocardiography correctly excluded or diagnosed the type of aortic dissection, ao… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1989
1989
2006
2006

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(1 citation statement)
references
References 20 publications
0
1
0
Order By: Relevance
“…Embolic phenomena occurs in 22-50% of cases of infective endocarditis [15]. Several studies with transesophageal echocardiography demonstrated a trend toward higher embolic rates with left-sided vegetation > 10 mm in diameter [16][17][18].…”
Section: Discussionmentioning
confidence: 99%
“…Embolic phenomena occurs in 22-50% of cases of infective endocarditis [15]. Several studies with transesophageal echocardiography demonstrated a trend toward higher embolic rates with left-sided vegetation > 10 mm in diameter [16][17][18].…”
Section: Discussionmentioning
confidence: 99%